2012
DOI: 10.1590/s0365-05962012000500005
|View full text |Cite
|
Sign up to set email alerts
|

DRESS: clinicopathological features of 10 cases from an University Hospital in São Paulo

Abstract: BACKGROUND: Drug reaction with eosinophilia and systemic symptoms is a severe form of drug-induced reaction with multiorgan involvement. OBJECTIVES: The aim of this study is to evaluate the epidemiological, clinical and pathological features and prognosis of this drug reaction among patients seen at a dermatology service. METHOD: Retrospective review of medical records of ten patients diagnosed with drug reaction with eosinophilia and systemic symptoms at the Federal University of São Paulo, from august 2008 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
3
11
0
3
Order By: Relevance
“…Patients were predominantly male, as observed in other small series investigated elsewhere, but in contrast with studies involving a large number of patients, in which females predominated . This variability, however, may have been circumstantial.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Patients were predominantly male, as observed in other small series investigated elsewhere, but in contrast with studies involving a large number of patients, in which females predominated . This variability, however, may have been circumstantial.…”
Section: Discussionmentioning
confidence: 49%
“…Phenytoin was the leading cause of DRESS/DIHS, albeit to a lesser extent than in other studies . Several investigations have identified aromatic anticonvulsants as the drugs that most often lead to DRESS/DIHS, while other studies conducted in Taiwan revealed allopurinol as the most commonly implicated drug …”
Section: Discussionmentioning
confidence: 74%
“…Bu çalışmada takip edilen hastaların tamamında sorumlu ilaç aromatik antikonvülzanlardı. Bizim hastalarımıza benzer şekilde Brezilya'da da fenitoinin en sık sorumlu ilaç olduğu bildirilmiştir 5 . Yang ve ark.…”
Section: Discussionunclassified
“…Deri belirtilerinin spektrumu çok geniştir. Sendromun kliniği tam olarak geliştiğinde, şiddetli mukokutanöz düküntüye ek olarak, ateş, lenfadenopati (LAP), hematolojik bozukluklar ve iç organ tutulumları görülebilir 4,5 . Farklı organ tutulumları ve deri bulgularının çeşitliliği nedeniyle DRESS sendromunun tanısı zordur 2,6 .…”
Section: Introductionunclassified
“…çalışmasında da DRESS sendromuna en sık neden olan ilacın fenitoin olduğu bulunmuştur. 9 Ülkemizde de Emre ve ark'nın 11 olguluk DRESS sendromu serilerinde tüm hastalarında etyolojik ajanın fenitoin olduğu bulunmuştur. 10 Bizim olgumuzda da literatür desteklenir şekilde DRESS sendromu fenitoin kullanımı sonrası meydana gelmiştir.…”
Section: Olguunclassified